1977
DOI: 10.1159/000122666
|View full text |Cite
|
Sign up to set email alerts
|

Comparative in vitro Studies on Corticotropin Releasing Activity of Vasopressin and Hypothalamic Median Eminence Extract

Abstract: The in vitro corticotropic releasing effects of vasopressin (VP) and hypothalamic median eminence (HME) extract were compared as a function of their concentration and preincubation and incubation times. Whereas HME extract augmented the ACTH secretion from non-preincubated adenohypophyses, VP released corticotropin from the pituitaries only after a 2 h preincubation period. The disappearance of endogenous VP during the preincubation time rendered the gland responsive. The maximal stimulation of ACTH secretion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
2

Year Published

1978
1978
1999
1999

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 4 publications
0
15
0
2
Order By: Relevance
“…Finally, pituitary desensitization to AVP may occur (similar to what has been shown for CRF in in vivo animal studies) independently of any steroid feedback (45). The anterior pituitary contains specific receptors for AVP which are distinct from those for hypothalamic CRF (46,47), and prior injections of AVP might cause down-regulation of the AVP specific receptor on pituitary cells (47). To determine which, if any, of the explanations is correct will require further study.…”
Section: Discussionmentioning
confidence: 83%
“…Finally, pituitary desensitization to AVP may occur (similar to what has been shown for CRF in in vivo animal studies) independently of any steroid feedback (45). The anterior pituitary contains specific receptors for AVP which are distinct from those for hypothalamic CRF (46,47), and prior injections of AVP might cause down-regulation of the AVP specific receptor on pituitary cells (47). To determine which, if any, of the explanations is correct will require further study.…”
Section: Discussionmentioning
confidence: 83%
“…The conten: of AVP in effluent media was measured by means of a specific radioimmunoassay, at 3 different dilutions as previ ously described [9], Results depicted in the figures are related to a representative experiment, which was repealed at least 3 limes. A composite graph is shown, that summarizes data from 3-7 experi ments per group and gives the peak secretion of AVP as the percen tage of basal release of the peptide.…”
Section: Methodsmentioning
confidence: 99%
“…Re-examination of CRF concentration us ing AVP-AS showed that it was still highest in ME, but was significantly higher in PVN than in SON, SCN and ARC. These results suggest that the PVN is an important nucleus for producing corticotropin-releasing hormone.The relationship between vasopressin and corticotropin releasing factor (CRF) is being discussed again in the litera ture, although many investigators have suggested that vaso pressin differs from authentic CRF [2,20,27, 30]. Vasopres sin-and neurophysin-containing fibers were found in large numbers in the external layer of the median eminence (ME) and many fibers terminated on the primary portal plexus [7, 35].…”
mentioning
confidence: 99%